Panic Buying as a Cause of Inflation According to al-Maqrizi's Perspective - Dahliana, Difi (Al-Tijary, 2022)
The research was motivated by the phenomenon of panic buying that hit the whole world at the start of the COVID-19 pandemic, but studies on panic buying in Islamic economic discourse are still very limited, and no one has linked it to the theory of inflation from an Islamic perspective. Therefore, this study aims to classify panic buying as the cause of inflation from al-Maqrizi's perspective. This research uses qualitative methods with a literature study. The results showed that panic buying can be classified as "human error inflation." Finally, the government must be more agile in preventing panic buying, and individuals must prioritize rationality over being isrof or tabzir. Panic buying has all the criteria that can be used as a reference for classifying human error as inflation. Ultimately, this research provides valuable insights and the implication of that it is important for government to have a policy to be more responsive to avoid things that can trigger panic buying.